2022
DOI: 10.1155/2022/2071326
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of the Effect of Laparoscopic Cholecystectomy for Acute Cholecystitis after Percutaneous Transhepatic Gallbladder Puncture and Drainage

Abstract: Objective. To assess the effect of laparoscopic cholecystectomy for acute cholecystitis after percutaneous transhepatic gallbladder drainage (PTGBD). Methods. A total of 70 patients with acute cholecystitis diagnosed and treated in our hospital between April 2020 and November 2021 were recruited and assigned to receive either conventional treatment (conventional group) or PTGBD plus laparoscopic cholecystectomy (experimental group) according to the order of admission (with January 2021 as the cut-off time poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…In addition, 55.5% of our study participants had a body mass index (BMI) of 25 or higher. Accordingly, our findings indirectly support the adage that Cholelithiasis is more common among women over the age of 40 who are fertile and overweight [8][9][10]. When compared to other studies, including one that found an overall infection rate of 3.6%, our study's 12.2% risk of post-operative wound infection was extremely high.…”
Section: Discussionsupporting
confidence: 80%
“…In addition, 55.5% of our study participants had a body mass index (BMI) of 25 or higher. Accordingly, our findings indirectly support the adage that Cholelithiasis is more common among women over the age of 40 who are fertile and overweight [8][9][10]. When compared to other studies, including one that found an overall infection rate of 3.6%, our study's 12.2% risk of post-operative wound infection was extremely high.…”
Section: Discussionsupporting
confidence: 80%
“…Operative time: In this comprehensive analysis, all 24 studies[ 9 - 32 ] included a comparative assessment of operative times across the two groups. The heterogeneity test indicated a highly significant variance ( P < 0.00001, I² = 94%), thus indicating the application of a random-effects model for the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Conversion to open surgery rate: Twenty-two studies[ 9 , 10 , 12 - 28 , 30 - 32 ] compared the rate of conversion to open surgery between the two groups. The heterogeneity test results showed P = 0.005 and I² = 50%, indicating significant heterogeneity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi, as publisher, following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of systematic manipulation of the publication and peer-review process.…”
mentioning
confidence: 99%